2007
DOI: 10.1177/1744987107080455
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to and knowledge about pain and pain management, of nurses working with children with cancer: A comparative study between UK, South Africa and Sweden

Abstract: Pain is among the most common effects of cancer and its treatment. Children and young people with cancer often consider pain from procedures and treatment to be the worst aspect of their illness.This study aimed to i) identify and describe knowledge and attitudes to pain and pain management amongst nurses working with children with cancer and ii) compare the perspectives on pain and pain management of nurses from UK, South Africa and Sweden.at UNIV OF NORTH DAKOTA on June 27, 2015 jrn.sagepub.com Downloaded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
2
27
2
2
Order By: Relevance
“…[10] Previous studies have found that clinical experience influences knowledge of pain. [16,17] However, in the present study there was no significant relationship between overall pain knowledge and clinical experience. Other studies concurrently show no significant correlation between postgraduate years of experience and pain knowledge.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…[10] Previous studies have found that clinical experience influences knowledge of pain. [16,17] However, in the present study there was no significant relationship between overall pain knowledge and clinical experience. Other studies concurrently show no significant correlation between postgraduate years of experience and pain knowledge.…”
Section: Discussioncontrasting
confidence: 84%
“…However, despite the low response rate (13.25%) and the sample size being smaller than the targeted 272 required for a 95% confidence level, a sample of 207 gave a 90% confidence level, which is regarded as acceptable in surveys of the type described here. [16] The participants were all physiotherapists registered to practise in SA with a special interest in sports and/or orthopaedic manipulative physiotherapy. This study provides valuable information on a population group in which there is a paucity of evidence regarding pain knowledge.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Frykt for overmedisinering, frykt for tilvenning til opioider og engstelse for respirasjonsdepresjon, er noen av områdene det eksisterer mangelfulle kunnskaper innenfor (8,(14)(15)(16)(17). Studier fra Finland og Sverige viser at sykepleiere trenger mer kunnskap om farmakologisk og ikke-farmakologisk smertehåndtering (18,19). Videre vurderes og dokumenteres smerte mangelfullt i praksis (20) og myter, som at barn ikke føler smerte på samme måte som voksne, eksisterer fortsatt (8).…”
Section: Introduksjonunclassified
“…Such restrictions can also be a result of insufficient knowledge about pain management or how to cope with children with complex communication needs (Bornman & Donohue, 2013). A need for improved attitudes and knowledge about pain and pain management among nurses has been shown in several countries, including South Africa (Enskär et al, 2007;Thunberg, Buchholz, & Nilsson, 2015;Twycross & Collis, 2013). However, it is not known how other professionals working in South African school settings provide pain management interventions for children with CP.…”
Section: Literature Reviewmentioning
confidence: 99%